Dance imagery for technique and performance - Franklin, Eric N. 4 0 16; 5 (Champaign, IL : Human Kinetics, 1996)
Details the scientific principles underlying imaging--the notion that images in the mind can alter the physiology and neuromuscular behavior of the body--and explains, through 583 illustrated imagery exercises, how the practice can be applied to learning and teaching dance technique, improvisation, and choreography.
Includes bibliographical references (p. 249-250) and index.
Reference and Research Book News
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Study and teaching.;Study and teaching.;Study and teaching. -- Dance;Improvisation in dance.;Imagery (Psychology);Choreography;Exercise.;Dance;Imagination.;Exercise.; 20; 2